Univers fictionnel et tonalités du récit littéraire dans Parcelles de vie de Sosthène MOVA KAWEN. - Alexis KATAMBWA Mutombo, (IJRDO - Journal of Social Science and Humanities Research, 2022)
The study deals with the fonctional universe et tones of the litterary narrative in parts of life, title which puts together three short stories published by Sosthene Mova Kaven in 2018.In fact from, these three short stories,  appear three sources of inspiration, three main themes et three different literary tones.The first short story entitled « Fragmented » is of a sentimental inspiration. It is a narrative of a pathetic tone which treats the main theme of missed-love. Hyperbole, repetition, metaphor, allegory and imagery tell about suffering and violent feelings. They are expressive means the writer uses to transmit her message.The second short story is « The Usurpator ». It is of a socio-political inspiration  and of a satirical tone. The narrative develops the theme of mediocrity of socio-political actors.To laugh at those actors, the writer gathers exprssive means that follow : the comic of situation, the comic of gestures and the comis of words.  Besides those literary techniques, the writer uses irony, comparison, metalespe, personification and humour.The third short story « Innocentia », is of a social and cultural inspiration. And dominated by a polemic tone and the theme portrayed is that of murder of a noble man.The narrative highly symbolic, is told in the form of a trail. Metonymy, interrogation and the lexic of judiciary eloquence are some of stylistic techniques, the authoress uses to transmit her message vehicle.